Understanding the staff behaviours that promote quality for older people living in long term care facilities: A realist review. (May 2021) - Haunch, Kirsty; Thompson, Carl; Arthur, Antony; Edwards, Paul; Goodman, Claire; Hanratty, Barbara; Meyer, Julienne; Charlwood, Andy; Valizade, Danat; Backhaus, Ramona; Verbeek, Hilde; Hamers, Jan; et al.
Abstract: Background: Little is known about how the workforce influences quality in long term care facilities for older people. Staff numbers are important but do not fully explain this relationship. Objectives: To develop theoretical explanations for the relationship between long-term care facility staffing and quality of care as experienced by residents. Design: A realist evidence synthesis to understand staff behaviours that promote quality of care for older people living in long-term care facilities. Setting: Long-term residential care facilities Participants: Long-term care facility staff, residents, and relatives Methods: The realist review, (i) was co-developed with stakeholders to determine initial programme theories, (ii) systematically searched the evidence to test and develop theoretical propositions, and (iii) validated and refined emergent theory with stakeholder groups. Results: 66 research papers were included in the review. Three key findings explain the relationship between staffing and quality: (i) quality is influenced by staff behaviours; (ii) behaviours are contingent on relationships nurtured by long-term care facility environment and culture; and (iii) leadership has an important influence on how organisational resources (sufficient staff effectively deployed, with the knowledge, expertise and skills required to meet residents' needs) are used to generate and sustain quality-promoting relationships. Six theoretical propositions explain these findings. Conclusion: Leaders (at all levels) through their role-modelling behaviours can use organisational resources to endorse and encourage relationships (at all levels) between staff, residents, co-workers and family (relationship centred care) that constitute learning opportunities for staff, and encourage quality as experienced by residents and families.